2014
DOI: 10.1002/bies.201400003
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome replication origins: Do we really need them?

Abstract: Replication of the main chromosome in the halophilic archaeon Haloferax volcanii was recently reported to continue despite deletion of all active replication origins. Equally surprising, the deletion strain grew faster than the parent strain. It was proposed that origin-less H. volcanii duplicate their chromosomes via recombination-dependent replication. Here, we recall our present knowledge of this mode of chromosome replication in different organisms. We consider the likelihood that it accounts for the viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The deletion of single origins resulted in only mild growth rate reductions (Hawkins et al, 2013), as observed in other archaea (Samson et al, 2013;Wu et al, 2014). In contrast, deletion of multiple origins resulted in improved growth rates, and a derivative in which all replication origins were deleted grew faster than wild type cells, an effect that appears to be driven by recombination-dependent replication (Hawkins et al, 2013), replication that initiates at recombination intermediates (Hawkins et al, 2013;Michel and Bernander, 2014).…”
Section: Dna Replication In Cells Without Active Replication Originsmentioning
confidence: 82%
“…The deletion of single origins resulted in only mild growth rate reductions (Hawkins et al, 2013), as observed in other archaea (Samson et al, 2013;Wu et al, 2014). In contrast, deletion of multiple origins resulted in improved growth rates, and a derivative in which all replication origins were deleted grew faster than wild type cells, an effect that appears to be driven by recombination-dependent replication (Hawkins et al, 2013), replication that initiates at recombination intermediates (Hawkins et al, 2013;Michel and Bernander, 2014).…”
Section: Dna Replication In Cells Without Active Replication Originsmentioning
confidence: 82%
“…H. volcanii was later found to be in possession of a third origin, and was remarkably also shown be able to replicate with all three origins deleted (Hawkins et al ., ). Rolf discussed the implications of this finding in a posthumously published article (Michel and Bernander, ).…”
Section: Fruitful Collaborations In Recent Yearsmentioning
confidence: 94%
“…An alternative explanation for RDR is activation of dormant origins randomly in cells so that no preferential origin emerged at the level of a cell population [29,30]. In this scenario the essentiality of RadA could imply that randomly-initiated replication forks more often collapse and have to be restarted.…”
Section: Are Replication Origins Essential For Viability In Archaea?mentioning
confidence: 99%